Fork on the Road: National Security as One of the Driving Forces behind Thailand’s Unilateral Move towards the Myanmar Crisis - Manullang, Abel Josafat; Sudirman, Arfin; Rifawan, Affabile (Papua Journal of Diplomacy and International Relations, 2024)
In June 2023, Thailand took a unilateral move to engage with Myanmar’s junta government, surprising ASEAN. It occurred in the midst of the lack of progress that ASEAN has made in addressing the Myanmar crisis, which directly affects Thailand as Myanmar’s closest neighbor. Although Thailand’s move did not worsen the situation, other ASEAN countries criticised it as going against ASEAN’s stance on the crisis. This article argues that Thailand’s decision was largely driven by concerns about its own national security. In terms of the research method, this article employs a qualitative approach. In particular, national security concepts and rational choice theory are employed to build the analysis. Using secondary data, this study shows how the Myanmar crisis impacts Thailand’s security, such as refugee inflows and airspace violations. ASEAN’s lack of progress, Thailand’s experience in engaging with Myanmar, and the presence of a precedent by Cambodia can also be seen as some of the driving forces behind its eventual move. KEYWORDSMyanmar crisis; National security; Rational choice theory; Thailand; Unilateral move